A method for determining right ventricle stroke volume - O. K. Rahmat, Rahmita Wirza; Abboud, Anas A.; Dimon, Mohd Zamrin; Kadiman, Suhaini; Saripan, M. Iqbal; Abdullah, Lili Nurliyana (2012)
The present invention relates to a method for determining right ventricle stroke volume comprising the steps of: providing a plurality of three-dimensional images of right cardiac ventricle of a patient over a cardiac cycle; identically slicing each of the plurality of images; selecting an image from the plurality of images, for each time unit of the cardiac cycle; determining a region of interest in each slice of the selected images, wherein the region of interest shows the right ventricle of the patient; determining area of the region of interest; determining volume of the region of interest; determining total volume of the region of interest for each time unit, wherein the maximum total volume is end diastolic volume and the minimum total volume is end systolic volume; and determining the right ventricle stroke volume using an equation: Right Ventricle Stroke Volume = end diastolic volume - end systolic volume (3).